METHODS OF PSYCHOLOGICAL APPROACH IN THE TRAINING OF YOUNG BOXERS - Pulatov Jamshid Abdumadjitovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the methods of psychological approaches to the training of young boxers, occurring in them individually - psychological states, as well as their psychocorrection. In addition, the article is aimed at studying the psychological and pedagogical requirements for the formation of athletes’ psychological activities, processes, personal states and characteristics that ensure the successful solution of training problems and participation in competitions.